2022
DOI: 10.46676/ij-fanres.v3i2.70
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Tomato Productivity in Western Oromia, Ethiopia: Evidence from Smallholder Farmers

Abstract: Tomato is one of the most important fruit vegetable crops in Ethiopia supporting the livelihood and improving the economic life of many farmers. However, the productivity of the crop is low due to poor production management practices, limitations in the availability of pesticides and fungicides, limitations to access information, market fluctuation, and shelf life of the crop. The study was undertaken in western Oromia to understand major factors affecting the tomato productivity of smallholder farmers. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Marginal effect result showed that as year of farming experience increase the allocative and economic efficiency increases by 0.0051 and 0.0039 respectively. This result is in line with the findings of previous studises; Senbeta et al(2022); Adewuyi and Amurtiya, (2021); Degefa et al(2020). The result further revealed that access to extension service was significantly influencing both technical (p<0.10) and economic (p<0.10) inefficiencies negatively.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Marginal effect result showed that as year of farming experience increase the allocative and economic efficiency increases by 0.0051 and 0.0039 respectively. This result is in line with the findings of previous studises; Senbeta et al(2022); Adewuyi and Amurtiya, (2021); Degefa et al(2020). The result further revealed that access to extension service was significantly influencing both technical (p<0.10) and economic (p<0.10) inefficiencies negatively.…”
Section: Resultssupporting
confidence: 92%
“…Technical efficiency measures the ability of a farm to obtain maximal output from a given set of inputs (output-oriented measures); or use the minimum feasible amount of inputs to produce a given level of output (input-oriented measures) Nakana et al( 2021); Onuche et al(2020);Gela et al(2019);Bhagavath (2009) and Coelli (1996).Allocative efficiency measures the ability of a farm to use inputs in optimal proportions given their respective prices and the production technology Adewuyi and Amurtiya (2021); Degefa et al(2020); Konja et al (2019) ;Coelli, (1996);Cooper et al (2004). Allocative inefficiency arises when inputs of production are used in a proportion that does not minimise the costs of producing a given level of output (Coelli et al, 2005) Economic efficiency is the product of technical efficiency and allocative efficiency.…”
Section: Theoretical Framework Productivity and Production Efficiencymentioning
confidence: 99%
“…Four types of fertilizer (NPS, NPSB, NPSBCa and NPSCa) are suggested for Yeki District. However, the map is suggested type of fertilizer but, the rate of those fertilizer in respective to crop type is not studied [45]. With this back ground, the present study was designed to evaluate the effect of NPSB fertilizer type on grain yield, nutrient use efficiency of maize and economic feasibility in Yeki district at Beko village Southwest of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the hydroponic method has been proven to solve this problem. Other benefits of having a hydroponic system include allowing farmers to manage water and nutrient supply with up to 90% efficiency, and the farmer can get yield year-round [4] [5]. Aside from that, hydroponics is a farming approach that can still be improved; its application is also simple to integrate with other systems such as fish farming (aquaponics), office areas, etc.…”
Section: Introductionmentioning
confidence: 99%